KONTRIBUSI PENDAPATAN USAHA VIRGIN COCONUT OIL (VCO) TERHADAP PENDAPATAN KELUARGA DI KECAMATAN KEWAPANTE KABUPATEN SIKKA NUSA TENGGARA TIMUR - Yunita, Maria; Kapa, Maximillian M.J.; Pellokila, Marthen Robinson (Undana Press, 2024)
Virgin Cococut Oil (VCO) has been researched to provide many benefits to the people of Kewapante District, and has an effect on family income, because VCO makes business a fairly good contribution to household income. This research aims to determine:1) VCO business income, and 2) VCO business contribution in Kewapante District, Sikka Regency, East Nusa Tenggara. The research location was carried out in Waiara Village and Wairkoja Village, Kewapante District. Determining the location deliberately (purposive sampling). The sample was taken as a whole from the population with a consideration of 30 respondents. The data used is primary data and secondary data. Data analysis uses descriptive analysis, including income and contribution analysis. The research results show that: 1) the average income of the Virgin Coconut Oil (VCO) business is Rp.12.906.133, per year. 2) Virgin Coconut Oil (VCO) business contribution is 46,73%. This means that the Virgin Coconut Oil (VCO) business makes a large contribution to total household income in the medium category.